2017
DOI: 10.1002/dmrr.2925
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide mitigates TNF‐α induced pro‐atherogenic changes and microvesicle release in HUVEC from diabetic women

Abstract: TNF-α induced pro-atherogenic alterations are amplified in endothelial cells chronically exposed to hyperglycemia in vivo. Liraglutide mitigates TNF-α effects and reduces cell stress/damage indicators, such as endothelial microvesicle (EMV) release. These results foster the notion that Liraglutide could exert a protective effect against hyperglycemia and inflammation triggered endothelial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 51 publications
2
33
1
Order By: Relevance
“…While the mechanisms that mediate the biological effects of EVs on their cellular targets remain poorly known, it is clear that EVs are implicated in most, if not all, physiopathological processes, including signal transduction, cell growth, and differentiation, metabolic regulation, embryofetal development, organogenesis, tissue homeostasis and repair/regeneration, antigen presentation and immune response, ageing, pathogen-host interactions, carcinogenesis, tumor invasion/metastasis, cardiovascular dysfunction, etc. [9,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. The EV cargo, packaged within relatively stable membrane-bound structures, is sheltered from degradation by the extracellular enzymes present in biological fluids, and may therefore maintain biological stability over comparatively long periods of time [38].…”
Section: General Characteristics and Biological Significance Of Evsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the mechanisms that mediate the biological effects of EVs on their cellular targets remain poorly known, it is clear that EVs are implicated in most, if not all, physiopathological processes, including signal transduction, cell growth, and differentiation, metabolic regulation, embryofetal development, organogenesis, tissue homeostasis and repair/regeneration, antigen presentation and immune response, ageing, pathogen-host interactions, carcinogenesis, tumor invasion/metastasis, cardiovascular dysfunction, etc. [9,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. The EV cargo, packaged within relatively stable membrane-bound structures, is sheltered from degradation by the extracellular enzymes present in biological fluids, and may therefore maintain biological stability over comparatively long periods of time [38].…”
Section: General Characteristics and Biological Significance Of Evsmentioning
confidence: 99%
“…Surface phosphatidylserine is a signal for recognition and uptake by adjacent cells, particularly professional phagocytes [96]; therefore, the half-life of these MVs is generally short. The distinctive biogenetic process accounts for the fact that MVs can be readily sub-classified based on annexin V positivity, restricted to MVs that expose phosphatidylserine, and patterns of surface markers, which generally reflect those of the parental cells [27,33,47]. However, phosphatidylserine is also exposed on apoptotic bodies, which are larger vesicles specifically formed during the late stages of apoptosis [97,98].…”
Section: Microvesicles and Apoptotic Bodiesmentioning
confidence: 99%
“…It has been observed that, when microvesicles are released by activated cells, the phosphatidylserine is flopped to the outer leaflet of the plasma membrane bilayer. For this reason, it exists as a subset of microvesicles that can be identified for the positivity to Annexin V, which is a molecule able to bind phosphatidylserine [4,22,32]. Phosphatidylserine is also expressed by apoptotic body membranes, and for this reason, the positivity to Annexin V (which is related to the surface exposure of phosphatidylserine) is not a useful method that allows to distinguish apoptotic bodies and microvesicles derived from activated cells.…”
Section: Extracellular Vesicles Subtypesmentioning
confidence: 99%
“…In coronary endothelial cells taken from subjects with T2D, Exendin‐4 could augment endothelial nitric oxide synthase (eNOS) phosphorylation and nitric oxide (NO) production—pathways that are known to lead to vascular relaxation . Glucagon‐like peptide 1 [7‐36 amide] and liraglutide can exert a protective effect against endothelial dysfunction induced by hyperglycaemia and/or inflammation through a reduction of tumour necrosis factor‐α (TNF‐α)‐induced nuclear factor‐κB activation. This can decrease inflammatory gene expression, including vascular cell adhesion molecule‐1 and monocyte chemoattractant protein‐1 .…”
Section: Myocardial Infarctionmentioning
confidence: 99%